BAKTERIOFAG DAN APLIKASI DALAM MENGENDALIKAN BAKTERI PATOGEN UNTUK MENINGKATKAN KEAMANAN PANGAN - Affan Gaffar; Elsa Mega Suryani (LPPM Universitas Negeri Jakarta, 2022)
Food safety and sustainable food production is an essential parts of the sustainable development goals of protecting the health and well-being of humans, animals, and the environment. Foodborne diseases are a significant cause of morbidity and mortality, particularly with the global crisis of antibiotic resistance. Bacteriophages as a biocontrol are a promising alternative for reducing contamination from pathogenic bacteria in food such as Escherichia coli, Bacillus cereus, Staphylococcus aureus, and Listeria monocytogenes. Bacteriophages are natural predators of bacteria that are harmless to humans and animals and are found in various environments, thus have been recognized as promising antimicrobial agents to help control specific bacterial pathogens in food production. Several bacteriophages have been applied in food to reduce the number of pathogenic bacteria. The results of this application show the efficacy of bacteriophages as biopreservation agents against foodborne pathogenic bacteria.